Evolution of oviposition behavior in gypsy moth (Lymantria dispar) in Hyrcanian forests, North of Iran (Biodiversitas Journal of Biological Diversity, 2016)
Hajizadeh G, Kavosi MR, Jalilvand H. 2013. Evolution of oviposition behavior in gypsy moth (Lymantria dispar) in Hyrcanian forests, North of Iran. Biodiversitas 14: 101-105. Oviposition behavior has been introduced at the center of many of the major debates on the ecology and evolution of interactions between insects and plants. The objective of this research was to determine the number of egg masses gypsy moth in relation to diameter at breast height (dbh), egg placement, orientation and host tree species. Sampling was carried out in Daland national park, Gorgan province. By global position system (GPS) device using polygons with width of 20 m and determined azimuth, defoliated trees were recorded. Data and means were compared using Duncan's multiple range tests. Results showed that the diameter at breast height was not significantly affected by the number of egg masses. The effect of oviposition place on number of egg masses gypsy moth were significant (P